Functional insights into Silymarin as an antiviral agent against Enterovirus A71 (EV-A71) - Lalani, S.*; Masomian, Malihe *; Poh, Chit Laa * (MDPI, 2021)
Enterovirus A71 (EV-A71) is a major neurovirulent agent capable of causing severe hand, foot and mouth disease (HFMD) associated with neurological complications and death. Currently, no FDA-approved antiviral is available for the treatment of EV-A71 infections. The flavonoid silymarin was shown to exert virucidal effects, but the binding site on the capsid was unknown. In this study, the ligand interacting site of silymarin was determined in silico and validated in vitro. Moreover, the potential of EV-A71 to develop resistance against silymarin was further evaluated. Molecular docking of silymarin with the capsid of EV-A71 indicated that silymarin binds to viral protein 1 (VP1) of EV-A71, specifically at the GH loop of VP1. The in vitro binding of silymarin with VP1 of EV-A71 was validated using recombinant VP1 through ELISA competitive binding assay. Continuous passaging of EV-A71 in the presence of silymarin resulted in the emergence of a mutant carrying a substitution of isoleucine by threonine (I97T) at position 97 of the BC loop of EV-A71. The mutation was speculated to overcome the inhibitory effects of silymarin. This study provides functional insights into the underlying mechanism of EV-A71 inhibition by silymarin, but warrants further in vivo evaluation before being developed as a potential therapeutic agent.